1990
DOI: 10.1002/ccd.1810210205
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of left atrial thrombi in mitral valve disease by coronary arteriography

Abstract: Arteriographic findings of neovascularity and fistula formation between coronary arteries and left atrium have occasionally been described in association with left atrial thrombosis in patients with mitral valve disease. The validity of these coronary arteriographic findings in diagnosis of atrial thrombi has been evaluated in 112 patients with mitral valve disease. Comparison was made with surgery. The study furnished these diagnostic values: sensitivity 70%, specificity 85%, positive predictive value 72%. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Interestingly, the occurrence of neovascularity and fistula formation from the coronary arteries to the LA, as documented in both retrospective studies and case reports, highlights a complex aspect of atrial thrombosis in patients with mitral valve disease [13][14][15][16][17][18]. The precise mechanism underlying fistular formation and neovascularization remains unclear; however, numerous studies have suggested that neovascularity and the development of fistulas from the coronary arteries to the LA are commonly associated with organized atrial thrombosis in patients afflicted with mitral valve disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the occurrence of neovascularity and fistula formation from the coronary arteries to the LA, as documented in both retrospective studies and case reports, highlights a complex aspect of atrial thrombosis in patients with mitral valve disease [13][14][15][16][17][18]. The precise mechanism underlying fistular formation and neovascularization remains unclear; however, numerous studies have suggested that neovascularity and the development of fistulas from the coronary arteries to the LA are commonly associated with organized atrial thrombosis in patients afflicted with mitral valve disease.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Russo et al pointed out that arteriographic evidence of neovascularity and fistula connections between coronary arteries and the LA have occasionally been observed in association with LA thrombosis among patients with mitral valve disease. The relevance of these arteriographic findings for diagnosing atrial thrombi was assessed in 112 patients with mitral valve disease, with surgical comparisons also drawn [14]. While these angiographic observations support the diagnosis of atrial thrombosis, their detection during coronary arteriography in patients with mitral valve disease is considered beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…46 This phenomenon was also described in another retrospective analysis as well as several case re-ports. 34,[47][48][49][50] Whether this neovascularization is specific to patients with severe mitral valve disease is unknown but has not been reported in patients without. This potentially explains the peripheral contrast enhancement observed in our second patient.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular inter est is the presence of the intracavitary throm bus. Areas of neovascularity have been re ported in association with atrial [12][13][14][15] or ventricular thrombi [16]. Microscopic evalua tion of some left atrial thrombi with coronary neovascularization revealed vascular chan nels with endothelial linings [13], We have noted 2 additional patients with prior myo cardial infarction in whom neovasculariza tion was present at the site of an apical throm bus ( fig.…”
Section: Discussionmentioning
confidence: 99%